2015
DOI: 10.1007/s40521-015-0051-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Interventions in Asthma

Abstract: Asthma is a multifactorial chronic respiratory disease characterised by recurrent episodes of airway obstruction. The current management of asthma focuses principally on pharmacological treatments, which have a strong evidence base underlying their use. However, in clinical practice, poor symptom control remains a common problem for patients with asthma. Living with asthma has been linked with psychological co-morbidity including anxiety, depression, panic attacks and behavioural factors such as poor adherence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
0
8
0
1
Order By: Relevance
“… 25 The recurrence of poor self- further supports a recognised need for increased psychology input to assess patients and support HCPs. NHS England 26 have recently recommended health psychology as an essential component of the severe asthma team. Adequate psychology support is underfunded in an increasingly financially constrained health economy and provision for demand remains very limited.…”
Section: Discussionmentioning
confidence: 99%
“… 25 The recurrence of poor self- further supports a recognised need for increased psychology input to assess patients and support HCPs. NHS England 26 have recently recommended health psychology as an essential component of the severe asthma team. Adequate psychology support is underfunded in an increasingly financially constrained health economy and provision for demand remains very limited.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst there is a good scientific rationale for psychological interventions to treat dysfunctional breathing, it is difficult to carry out well-designed studies in this area and there is little supporting evidence for this approach in any age group (57, 58). Suggestion therapy has been shown to be highly effective in young children with habit cough using a bed sheet as a bandage to strap and heal the chest, but a similar device has not been used for dysfunctional breathing in asthma (59).…”
Section: Treatmentmentioning
confidence: 99%
“…Biofeedback therapy and psycho-education are also likely to be beneficial, through empowering experiences of effective coping, stress management, and relaxation (Pope et al, 2014;Smith et al, 2007), which may lead to increased self-efficacy (and reduced psychiatric morbidity). Systematic reviews on psychological interventions for asthma found that these methods may be effective, but were inconclusive due to small sample sizes and differing outcome measures (see Smith & Jones, 2015;Yorke et al, 2007). Future studies on interventions should more explicitly incorporate efficacy building and longitudinally measure changes in self-efficacy to further support the importance of self-efficacy for people with asthma, PTSD, and co-morbid disorders (Battersby et al, 2010;Marks et al, 2005;Taylor et al, 2014).…”
Section: Regression Analyses Of Locus Of Control and Self-efficacymentioning
confidence: 99%
“…Still, preliminary evidence points toward wellbeing and quality of life benefits from a range of psychological interventions for chronic health conditions. These include cognitive and behavioural approaches, relaxation, bio-feedback, and psychoeducation (Smith & Jones, 2015). However, the three systematic reviews in the past decade failed to find firm evidence for any one intervention due to small studies and suboptimal methods (see Smith and Jones, 2015).…”
Section: Introductionmentioning
confidence: 99%